‘Hidup Bersama’ atau Kebebasan Beragama dan Berkeyakinan: Larangan Penggunaan Penutup Wajah di Negara-Negara Eropa - Sajeed Fahurdeen (Jurnal HAM, 2025)
Many European States introduced general or specific bans on face covers and religious symbols in public schools, universities and public places. The ban on religious symbols and face covers in public places and educational institutions has escalated the tensions, disbelief and mistrust between adherents of different religions and beliefs. This paper applies a doctrinal legal research methodology mixed with desk research, analyzing international human rights instruments and important landmark judicial precedents to assess the legal scope and limitations on freedom of religion and belief and its consequences. Although limitations to freedom of religion and belief are permitted in human rights law, European States justified the limitations on the basis of ‘living together’ contrary to the provisions of the International Covenant on Civil and Political Rights. The acceptance of the conditionality of ‘living together’ by the European Court of Human Rights set a disturbing precedent and it is applied in different societies in enforcing the majoritarian view and undermining the rights of minorities. Although the Human Rights Committee determined that Article 18(3) of the International Covenant on Civil and Political Rights must be strictly interpreted and the term ‘living together’ is a vague concept and made recommendations, the European State parties have not taken any action to implement the recommendations. Since the Human Rights Committee has no power to enforce the recommendations, the mere essence of the treaty is negated, and it provides a dangerous precedent for other States around the globe to follow introducing limitations on the freedom of religion and belief.